A Review Article on Various Network Security Systems and Solution: Exploring the Challenges and Solutions in Network Security (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Network security is one of the intense activity since none of the routing protocol can't completely anchor the way. For any network there are couple of malignant hub that can be make issue add up to network way likewise some time couple of hubs are over-burden to exchange expansive size of information packet. This paper represented few existing secured routing protocols to recognize how to recoup this noxious hub from the system and discover a protected information way.